PNBE do professor: livros e bibliotecas para a formação docente - Piedade, Amir Aparecido dos Santos (2018)
This research analyses the PNBE Teacher – The National School Library Program – 2010 and 2013 editions that acquired books that included the theory and methodology, designed to support the teaching of public schools teachers and also to encourage school libraries. Created by the Ministry of Education, this program was part of the public educational policy developed during the governments of presidents Lula and Dilma in order to contribute on the continuing education of Basic Education teachers. With the purpose of knowing the program and its implications in the continuing education of teachers, we have investigated the constitution of the school libraries and the book programs destined to public schools. It was through interviewing teachers in some schools that we tried to identify who was the professional to whom the program was designed: their education background, reading habits, knowledge of the PNBE Teacher, use of the school library. The impact of this program on publishing market and on books produced by authors to attempt the specificities of the call publications was also analyzed